Sharing idiosyncratic risk even though prices are “wrong” - Halim, Edward (2022)
We design an infinite-horizon dynamic asset market experiment with perishable consumption and a long-lived asset where gains from trade originate from individuals experiencing idiosyncratic income shocks. Our study is based on the consumption-based general equilibrium theory (Lucas (1978)). The presence of traders having induced motive to smooth consumption is not sufficient to eliminate price bubbles. Despite the asset being consistently priced higher than the equilibrium price, traders are able to share idiosyncratic risk and attain higher welfare. The co-existence of traders with income shocks along with those having no induced motive to trade does not hinder in the former smoothing their consumption stream. Our results hold for markets with and without aggregate risk.